The Learning Gap between Classroom Education and Artificial Intelligence-Based Education in Curriculum Design among Students of the College of Physical Education and Sports Sciences from the Students’ Perspective - Khadair , Yasir Hussein; Hamdan , Abduallah Ghazi (Journal of Physical Education, 2026)
The present study aimed to identify the learning gap between classroom-based education and artificial intelligence (AI)-based education among students of Colleges of Physical Education and Sports Sciences. It also sought to determine the effectiveness of classroom education and AI-based education in reducing the learning gap among these students. The research problem addressed the following questions: Are there statistically significant differences in the learning gap between students who learn through traditional classroom education and those who learn through AI-based education in Colleges of Physical Education and Sports Sciences? What is the nature of the learning gap between classroom education and AI-based education among these students? Which educational approach is more effective in reducing the learning gap? The results of the study indicated that there is a learning gap between classroom education and AI-based education among students of Colleges of Physical Education and Sports Sciences. The findings also revealed that the use of artificial intelligence technologies contributes to improving the quality of the educational process and enhancing the design of educational curricula. Furthermore, AI helps address individual differences among students by providing learning content that aligns with their needs and learning abilities. Based on these findings, the researcher recommends enhancing the integration of artificial intelligence in the educational process. AI technologies can provide advanced analytical tools that assist teachers in monitoring students’ progress and diagnosing learning difficulties more accurately. In addition, several challenges still hinder the effective implementation of AI in education, which requires further efforts to overcome these obstacles and promote the successful integration of AI technologies in educational environments.